Integrating Islamic Values, Child Rights, and Policies in Caring for Neglected Children - Ellya Susilowati (Senarai: Journal of Islamic Heritage and Civilization, 2025)
The issue of caring for neglected children represents a civilizational challenge, as the quality of a nation is measured by how it treats children who have lost parental care. This requires a childcare system rooted in moral values, human rights, and sustainable social policies. The aim of this study is to examine the care of neglected children through three main perspectives: Islam, the Convention on the Rights of the Child (CRC), and national as well as regional policies. The study employs a literature review method with a descriptive-analytical qualitative approach, analyzing texts and official documents such as the Qur’an, Hadith, national legislation, international conventions, national regulations, and recent academic studies. The findings reveal a convergence among the three perspectives, namely the recognition of children’s dignity, the protection of rights, and the emphasis on the best interests of the child. However, challenges remain, including institutional limitations, adaptation to digital disruption, and cultural contextual differences. This article concludes that integrating Islamic values, CRC principles, and national-regional policies is essential to developing a holistic, sustainable, and contextual childcare system for neglected children. The practical implications highlight the need to strengthen Child Welfare Institutions (LKSA), empower communities based on religious values, and harmonize regulations with child rights principles to ensure more effective protection of neglected children.